Supplementary data for Comparative genomics of Salmonella enterica serovars Paratyphi A, Typhi and Typhimurium reveals distinct profiles of their pangenome, mobile genetic elements, antimicrobial resistance and defense systems repertoire - Charles Coluzzi (19332067) (2025)
Supplementary data for Comparative genomics of Salmonella enterica serovars Paratyphi A, Typhi and Typhimurium reveals distinct profiles of their pangenome, mobile genetic elements, antimicrobial resistance and defense systems repertoire